Multi-criteria decision methods for CSR management – literature review - Doś, Anna (Managerial Economics, 2017)
Business today faces a managerial transition to adapt a new decision-making criterion and a course of action; namely, “corporate sustainability.” Corporate social responsibility can be embedded in (or fostered by) value-based management. In any case, adopting CSR as a part of a firm’s strategy and operations requires changed standards for decision-making. Decision-makers face the challenge of following tangible and intangible goals of multiple stakeholders. This study provides insights into how multi criteria decision tools can be harnessed to operationalize CSR. The method applied in the article is a systematic international literature review. The findings suggest that papers aimed at using MCDM to enhance CSR management are mostly newer publications. Three important research avenues have emerged. In the first avenue, MCDMs are seen and used to enhance managerial decisions where a number of heterogenic goals must be achieved. The second avenue is where MCDMs are seen and used to evaluate a firm’s quantitative and qualitative outcomes in terms of values created for multiple stakeholders. The third trend is connected with sustainable supply-chain management.